Analisis Implementasi Kebijakan Insentif Pajak Umkm Dalam Rangka Meningkatkan Kepatuhan Wajib Pajak UMKM Di Wilayah Kelurahan Margasari Kota Tangerang - Endah Budiastuti; Martina Safitri (Jurnal Pajak Vokasi (JUPASI), 2023)
The spread of corona virus cases has a big impact on the economy, especially for the lower middle class and MSMEs. And to restore the MSME economy in Indonesia, the Indonesian government took the initiative to help MSMEs carry out their obligations in tax payments and reporting, while still growing the level of compliance, awareness and obedience of MSME taxpayers. Therefore, PP No. 23 year 2018 was formed to provide instruction regarding MSME tax payment and then a policy regarding the tax incentives was issued which was contained in PMK No. 23 year 2020 which was been changed to PMK No. 44 year 2020. However, a new regulation was issued in the HPP Law regarding providing tax incentives and Final Income Tax. The purpose of providing tax incentives is to increase the compliance of taxpayer in carrying out their obligations. So, the purpose of this research is to find out the implementation of the MSME tax incentive policy provided by the government during the COVID-19 pandemic as well as the obstacles encountered and the efforts made in dealing with the obstacles that occurred. And the used method is descriptive qualitative method, namely analyzing the implementation of MSME tax incentive policy and the results of interviews from the informants. The used data is data from KPP Pratama of West Tangerang and MSMEs in Margasari Sub-District. The results of this study are the implementation of this tax incentive policy has been going well, this is because the KPP Pratama of West Tangerang really maintains the communication with taxpayers and carries out their duties in accordance with what has been determined. However, in the process of the tax incentive policy implementation, there are still obstacles such as the lack of knowledge of taxpayers, the use of technology that is not understood by taxpayers and the level of awareness of taxpayers is low. And the efforts are being made, such as conducting the socialization to taxpayers, providing the notification of due dates.